The role of the Bolsheviks in preserving Russia’s integrity (February-October 1917) - Vladimirovich, Kholyaev Sergey; Alekseevna, Lichak Natalija (Opción, 1970)
This article presents the authors' view on the understanding the deep revolutionary crisis during the first eight months of 1917. The purpose of the study is to show a deep split in society as a result of the collapse of the monarchy, the intensification of power struggles between different political forces in Russia in 1917, the decentralization of the state, the transformation of the Bolsheviks into the main subject of preservation of the integrity of the country. In February 1917, anarchy, chaos, and the beginning of the process of decomposition of the state's integrity became a threat to the country. Bolsheviks' political activities of 1917 were the only way out of the critical situation faced by Russia, which allowed to save the link of several episodes of the Russian history that was almost devastated by the events of February 1917.